Evaluation of salivary acetylcholinesterase and pseudocholinesterase in patients with Alzheimer's disease: A case–control study. (11th December 2018) - Ahmadi‐Motamayel, Fatemeh; Goodarzi, Mohammad Taghi; Tarazi, Shabnam; Vahabian, Mehrangiz
Abstract: Aim: The aim of this study was to evaluate acetylcholinesterase (AChE) and pseudocholinesterase (PChE) in whole saliva in patients with Alzheimer's disease (AD) and in healthy subjects. Saliva has a high potential for keeping track of general health and diseases. AD is a type of dementia with reduction in brain cholinergic markers that causes memory, thinking, and behavior problems. Up to 90% decrease in AChE activity has been observed in AD. Methods and results: Thirty healthy subjects and 30 patients with AD participated in this study. Saliva samples were collected from 8 to 10 am . AChE and PChE of saliva were assessed by the Ellman method. Statistical comparison was performed using SPSS 16 for t ‐test. The activity of AChE and PChE significantly increased in the group with AD compared to the healthy subjects. Sex had no effect on the activities of these enzymes. No correlation existed between the duration of illness and enzymatic activity. The enzyme levels reduced with age. Conclusion: AChE and PChE levels were increased in saliva samples of patients with AD. Therefore, saliva has the potential for being used for the purpose of biomarker evaluation to replace cerebrospinal fluid in patients with AD.